Environmental DNA reveals a multi‐taxa biogeographic break across the Arabian Sea and Sea of Oman. Issue 1 (20th September 2021) - DiBattista, Joseph D.; Berumen, Michael L.; Priest, Mark A.; De Brauwer, Maarten; Coker, Darren J.; Sinclair‐Taylor, Tane H.; Hay, Amanda; Bruss, Gerd; Mansour, Shawky; Bunce, Michael; Goatley, Christopher H. R.; Power, Matthew; et al.
Abstract: Environmental DNA (eDNA) is increasingly being used to assess community composition in marine ecosystems. Applying eDNA approaches across broad spatial scales now provide the potential to inform biogeographic analyses. However, to date, few studies have employed this technique to assess broad biogeographic patterns across multiple taxonomic groups. Here, we compare eDNA‐derived communities of bony fishes and invertebrates, including corals and sponges, from 15 locations spanning the entire length of the Omani coast. This survey includes a variety of habitats, including coral and rocky reefs, and covers three distinct marine ecoregions. Our data support a known biogeographic break in fish communities between the north and the south of Oman; however, the eDNA data highlight that this faunal break is mostly reflected in schooling baitfish species (e.g., sardines and anchovies), whereas reef‐associated fish communities appear more homogeneous along this coastline. Furthermore, our data provide indications that these biogeographic breaks also affect invertebrate communities, which includes corals, sponges, and broader eukaryotic groups. The observed community shifts were correlated with local environmental and anthropogenic differences characteristic of this coastline, particularly for the eDNA‐derived bony fish communities. Overall, this study provides compelling support that eDNA sequencing and associated analyses may serve as powerful tools to detect community differences across biogeographic breaks and ecoregions, particularly in places where there is significant variation in oceanographic conditions or anthropogenic impacts. Abstract : We conducted a multi‐marker eDNA metabarcoding survey across the coastline of Oman to assess whether eDNA‐derived fish and invertebrate communities reflected a biogeographic break between the north and the south of Oman. The eDNA data indicated that this faunal break is mostly reflected in schooling baitfish species but also included corals, sponges, and broader eukaryotic groups. The observed community shifts showed some correlation with local environmental and anthropogenic differences characteristic of this coastline, particularly for the eDNA‐derived fish communities.